The Role of NT-proBNP in the Diagnosis of Ventricular Arrhythmias in Patients with Systemic - Lucian MURESAN; Ana PETCU; Crina MURESAN; Mirela RINZIS; Gabriel GUSETU; Dana POP; Dumitru ZDRENGHEA; Simona REDNIC (Tehran University of Medical Sciences, 2017)
Background: In patients with systemic sclerosis, NT-proBNP is a useful diagnostic marker for pulmonary hypertension and ventricular dysfunction, with important prognostic significance. The aim of this study was to assess the relationship between the NT-proBNP levels and the presence and severity of ventricular arrhythmias in patients with scleroderma. Methods: Forty consecutive patients with a diagnostic of systemic sclerosis according to the EULAR criteria admitted at the Rheumatology Clinic of Cluj-Napoca, Romania, from Jan 2014 to Apr 2014 were enrolled. Patients underwent a 12-lead ECG and a 24-hour Holter ECG monitoring for ventricular arrhythmias evaluation. Blood sample testing (including NT-proBNP level measurements), echocardiography, spirometry, chest X-ray and, when considered appropriate, high-resolution chest CT were performed. Results: Sixty percent of patients (n=24) had abnormal NT-proBNP serum levels (>125 pg/ml) and 10 patients had >100 PVC /24 h. There was a statistically significant correlation between the NT-proBNP levels and the total number of premature ventricular contractions (PVC) (r=0.445, P=0.006), total number of isolated PVC (r=0,493, P=0.002), total number of ventricular couplets (r=0.379, P=0.021) and the number of PVC morphologies (r=0.501, P=0.002). The presence of an NT-proBNP serum level >287 pg/ml had a sensitivity of 55% and a specificity of 93% in predicting the presence of complex ventricular arrhythmias on 24-hour Holter ECG monitoring. Conclusion: NT-proBNP levels could become a useful ventricular arrhythmia marker for assessing the arrhythmic risk in patients with systemic sclerosis.